2020
DOI: 10.3126/janr.v3i1.27003
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economics of wheat production in Kailali and Sunsari districts of Nepal

Abstract: For socio-economic assessment on wheat production, research was conducted from March to June, 2019 in two major wheat growing districts of Nepal, Kailai and sunsari. The primary information was collected by face to face interview using the pre-tested semi-structured interview schedule, two Key Informant Surveys were also done.In addition, the secondary information were collected from the review of related literatures. The survey areas were selected by consultating with Agriculture Knowledge Centre and agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Factors affecting the rice yield Findings of this study regarding positive effect of age of the household head on rice production is similar with the findings of Subedi et al (2020); with the increase in age, the farming experience increases, which might contribute to higher yield through better use of input resources and technology. Also, the study revealed that the farm households having their major occupation agriculture have higher yield as compared to their counterparts.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Factors affecting the rice yield Findings of this study regarding positive effect of age of the household head on rice production is similar with the findings of Subedi et al (2020); with the increase in age, the farming experience increases, which might contribute to higher yield through better use of input resources and technology. Also, the study revealed that the farm households having their major occupation agriculture have higher yield as compared to their counterparts.…”
Section: Discussionsupporting
confidence: 86%
“…The rice productivity (yield) was used as dependent variable whereas different socio-economic and demographic characteristics of the respondents were used as explanatory variables. Multiple regression models have been used in several studies to assess the factors affecting the crop yield (Adhikari et al, 2018;Subedi et al, 2020;Bhattarai et al, 2020). The multiple regression model specified in this study is, Y (rice yield) = f (age of the household head, gender of the household head, primary occupation of the household head, number of family members involved in agriculture, livestock standard unit, membership of any organization, subsidy from the government in inputs, area of rice cultivated land) Also, LnY = α0 + βiXi + ei Where; LnY = Rice yield (in natural log form) α0 = Constant βi = Coefficient Xi = Explanatory variables ei = Error term…”
Section: Assessment Of the Factors Affecting The Rice Productionmentioning
confidence: 99%
“…Nepal Agricultural Research Council has been recommended more than 40 improved varieties for different ecological regions of Nepal of which 17 for hill and 26 for terai region (Timsina et al, 2018). In terai region, more than 60% of wheat is produced among three regions of Nepal ( Subedi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%